FENOMENA LIVING QUR’AN: TAHFIDZ QUR’AN DI PESANTREN SUBULUSSALAM PLOSOKANDANG TULUNGAGUNG - Binti Khabibatur Rohmah Al Arifah; Robitoh Widi Astuti (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
The study of living Qur'an is a study that includes various social events related to the presence of the Qur'an in a Muslim community. The research problem in this article is the implementation of the tahfidz phenomenon, transmission and transformation and the meaning of the tahfidz phenomenon. This is unique in Pesantren Subulussalam. This article analyzes the phenomenon of living Qur'an in Pesantren Subulussalam which focuses on tahfidz Al-Qur'an. This research uses descriptive qualitative research. Tahfidz activities are carried out every day in ba'da maghrib and ba'da dawn. Ba'da maghrib is done muraja'ah and tartilan method. Ba'da subuh compulsory deposit and classical method. In addition, there is also a series of prayer activities using maqra'. Tahfidz students are rotated to become prayer imams in order to test memorization and train focus in muraja'ah. This research uses Karl Mannheim's sociological theory. The results found that the phenomenon of tahfidz in Pesantren Subulussalam has a characteristic to achieve the target of tahfidz students. Objective meaning, namely the activity has become a routine and the obligation of tahfidz students to follow a series of activities. Expressive meaning, namely the meaning proposed to the perpetrators to get the blessing of the Qur'an, get the blessing of Allah SWT, and as a medium to get syafa'at. As for the Documentary meaning, the activity has become a culture that has been passed down from generation to generation